Analisis Pengaruh Faktor Makroekonomi Terhadap Perdagangan Internasional - Shindy Oktavia; Cahya Fitra Sabrina; Dwi Ananda Pangesti; Cep Jandi Anwar; Indra Suhendra (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The purpose of this study was to determine the relationship between Inflation, Exchange Rates, and GDP on Imports in Indonesia in 1990-2022. Import is a government policy in the field of international trade that plays a role in increasing national economic growth. Indonesia has abundant natural resources. Indonesia should be able to meet its own needs with its natural resources, but instead depends on imported goods from other countries. Thus, the method used in this study is the Vector Autoregression (VAR) method, because this method is used to analyze a relationship between variables in which the independent and dependent variables cannot be ascertained. The data used is quantitative data, and the source is secondary data, for example data collected from websites such as the World Bank. The results of this study are that the GDP variable has a greater relationship to imports than the inflation and exchange rate variables.